Use advanced manufacturing technology to rationalize costs and reduce the time (Journal of Accounting and Financial Studies ( JAFS ), 2018)
Aim of this study (to provide a conceptual framework on advanced manufacturing .ukiewih the use of advanced manufacturing in the laboratory (7) which affects the costs and time required to produce a unit), and that the most important conclusion reached by the research that the use of advanced manufacturing technology leads to dwindling direct wage costs in terms of reducing number of employees and the elimination or reduction of production lines. Thus the use of advanced manufacturing technology leads to lower costs by 94% and 99% the time and the most important conclusion reached by the search company to adopt the use of advanced technology in the production process in the light of globalization and open markets on the global markets to meet the needs and desires of customer